Ant Fauna on Cecropia pachystachya Trécul (Urticaceae) Trees in an Atlantic Forest Area, Southeastern Brazil - Reis, Paula CJ; DaRocha, Wesley D; Falcão, Luiz AD; Guerra, Tadeu J; Neves, Frederico S (Sociobiology (Chico, CA), 2013)
Cecropia are pioneer successional trees frequently associated with ants. Generally a single dominant colony of Azteca ant inhabits each mature Cecropia tree, but other ant species may be found living or foraging on the same tree. In this study, we assessed the diversity of ant species on Cecropia pachystachya trees in two sites in the Brazilian Atlantic Forest: a dust-free roadside and a dusty roadside. We also investigated the influence of tree architecture on ant species richness. We found a total of 24 ant species distributed in 11 genera and five subfamilies on C. pachystachya trees; 18 in the dust-free roadside and 14 in the dusty roadside. We found up to five ant species on a single tree, but only Azteca alfari was frequently encountered. Ant species richness per tree did not differ significantly between sites and was related to tree architectural traits. On the other hand, ant species composition on trees differed significantly between sites. Our study indicates that heavy dust deposition on Cecropia trees may affect associated ant communities, not by changing ant species richness, but by causing different species to live and forage on trees under different dust exposure.